2018
DOI: 10.1155/2018/4645906
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Adjacent Level Spondylodiscitis after Initial Surgery with Instrumented Spinal Fusion: A Report of Three Cases and Review of the Literature

Abstract: To date, 2 cases of adjacent level spondylodiscitis occurring a few months after initial spinal fusion were reported. However, the development of delayed adjacent level spondylodiscitis is very rare. The authors report 3 cases of spondylodiscitis that occurred at the proximal adjacent level of the fused spine more than 1 year after the initial surgery. Antibiotic treatment was initially chosen in all three cases. In two of the cases, progressive neurological deficit occurred at the level of the infection due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 11 publications
(13 reference statements)
0
8
0
Order By: Relevance
“…ASI after surgery of spondylodiscitis is considered as a rare complication (1.94%) via a large cohort study [2]. ASI in uninfected spinal surgery should be rarer, and in fact, only four case reports introduced it in conventional spinal fusion surgery [3][4][5][6]. In this present case, the patient developed ASI two months after the initial instrumented lumbar fusion surgery and achieved satisfactory outcome via debridement operation and autograft bone implantation fusion after failed conservative treatment.…”
Section: Introductionmentioning
confidence: 63%
See 4 more Smart Citations
“…ASI after surgery of spondylodiscitis is considered as a rare complication (1.94%) via a large cohort study [2]. ASI in uninfected spinal surgery should be rarer, and in fact, only four case reports introduced it in conventional spinal fusion surgery [3][4][5][6]. In this present case, the patient developed ASI two months after the initial instrumented lumbar fusion surgery and achieved satisfactory outcome via debridement operation and autograft bone implantation fusion after failed conservative treatment.…”
Section: Introductionmentioning
confidence: 63%
“…According to Siam et al's study, the most commonly involved level was L3-4, the next were T12-L1 and L2-3. Nagoshi et al [6] reported three ASI cases which involved T11-12, L1-2, and L2-3. A case reported by Xin and He [5] occurred at level L3-4.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations